A Companion to American art - Davis, John 1961 September 24-; Greenhill, Jennifer A. 1974-; LaFountain, Jason David (Wiley Blackwell companions to art history, 2015)
A companion to American art presents 35 newly-commissioned essays by leading scholars that explore themethodology, historiography, and current state of the field of American art history.